STRUKTUR DAN PROSEDUR PENGORGANISASIAN KURIKULUM UNTUK PEMBELAJARAN BERKUALITAS - Anwar Hidayat; Agus Pahrudin; Sri Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Curriculum and learning organization is one of the key components in the education system that functions as a guideline in compiling, presenting, and implementing teaching materials in a structured manner. This study discusses in depth the concept of curriculum organization, its main objectives, various types of curriculum organizations such as subject curriculum, correlated curriculum, and integrated curriculum, as well as the steps in selecting and determining the right curriculum content. In addition, the curriculum preparation procedure is also described, starting from identifying needs to the evaluation stage. This study emphasizes that curriculum organization is not only related to the arrangement of lesson content, but must also pay attention to the harmony between educational objectives, student characteristics, and developing socio-cultural dynamics. The results of the discussion show that the success of curriculum implementation is highly dependent on the accuracy of the structure, relevance of the content, the use of effective learning methods, and the existence of continuous evaluation. With good and planned organization, the curriculum can become a solid foundation in supporting the achievement of quality, relevant, and adaptive education to global challenges